2016
DOI: 10.1016/j.neuroscience.2015.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Density of GFAP-immunoreactive astrocytes is decreased in left hippocampi in major depressive disorder

Abstract: Neuroimaging and postmortem studies of subjects with major depressive disorder (MDD) reveal smaller hippocampal volume with lengthening duration of illness. Pathology in astrocytes may contribute significantly to this reduced volume and to the involvement of the hippocampus in MDD. Postmortem hippocampal tissues were collected from 17 subjects with major depressive disorder and 17 psychiatrically-normal control subjects. Sections from the body of the hippocampus were immunostained for glial fibrillary acidic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(174 citation statements)
references
References 83 publications
9
161
2
2
Order By: Relevance
“…Astrocytes were further shown to contribute to the integration of adult-born neurons in the hippocampus, although adult hippocampal neurogenesis in humans remains controversial (Krzisch et al 2015;Sultan et al 2015;Sorrells et al 2018). Moreover, the involvement of hippocampal astrocytes and astrocyte-neuron interactions in Huntington's disease, major depressive disorder, and schizophrenia have been reported (Kolomeets and Uranova 2010;Cobb et al 2016;L'Episcopo et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes were further shown to contribute to the integration of adult-born neurons in the hippocampus, although adult hippocampal neurogenesis in humans remains controversial (Krzisch et al 2015;Sultan et al 2015;Sorrells et al 2018). Moreover, the involvement of hippocampal astrocytes and astrocyte-neuron interactions in Huntington's disease, major depressive disorder, and schizophrenia have been reported (Kolomeets and Uranova 2010;Cobb et al 2016;L'Episcopo et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Several other known effects of stress, including decreased numbers of inhibitory interneurons throughout the hippocampus (68), decreased numbers of glia in the neuropil (69), and decreased hippocampal microvasculature (70) are potential factors. Glial cells, particularly astrocytes, are reduced in number and size in both human depression and animal models of chronic stress (7173), suggesting a potential contribution to volume change.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem brain studies have consistently shown that the most important cellular abnormality in MDD is represented by reductions in glial cells and specifically in astrocytes, rather than neurons (Cobb et al, 2016;Ongur et al, 1998;Rajkowska and Stockmeier, 2013). Astrocytes (and especially protoplasmic astrocytes present in the gray matter) have a crucial role in regulating several energy-intensive processes involving neurons, including glucose metabolism, neurotransmitter uptake (particularly glutamate and the cycling from glutamate-glutamine), synaptic development and maturation, and the blood-brain barrier (Kettenmann and Ranson, 2005).…”
Section: Discussionmentioning
confidence: 99%